The Bridge21 model of technology-mediated, team-based, 21st century learning in post-primary classrooms in Ireland - CONNEELY, CLAIRE (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2018)
The classroom of the future is generally described in terms of the availability and use of the latest advances in technology as a central component, along with student-centred, skills-focussed pedagogies. A common pattern across many of the recent global reform programmes aimed at leveraging the potential of technology in schools is learning outcomes defined by proficiency in core subject knowledge and also by the development of 21st century skills, such as creativity, collaboration and problem-solving. Ireland is no exception, with many recent studies and reform programmes calling into question the structure and purpose of schooling in an education system characterised by rote-learning, formal assessments of traditional subjects in an overcrowded curriculum and the restricted teaching day and year that is typical at post-primary level (NCCA, 2005; McMurrow, 2006; Jeffers, 2011; Collins & Dolan, 2011; Smyth, 2016). Despite this, there has been a persistent dearth of practical, replicable models as to how such ideals might translate into practice in the authentic setting of the classroom. Professional development (PD) in an era of reform must provide teachers with the opportunity to reflect critically on their practice and to develop new knowledge and beliefs about content, pedagogical approaches, role identity, student outcomes and what it means to be a learner (Ertmer, 2005; Ertmer & Ottenbreit-Leftwich, 2010; Voogt, Knezek, Cox, Knezek & ten Brummelhuis, 2013; Prestridge, 2012). The most effective programmes of professional development tend to be those that are grounded in collective professional discourse focussed on shared experiences and practice (Little, 2003). Teachers typically look towards resources, practical designs and collegial support in bringing about change in their classrooms. Bridge21 is a learning model that resonates with much of the literature on 21st century learning. Developed in 2007, it is centred on the rationale that technology has the potential to support a structured collaborative, project-oriented, learning context. The core components of a Bridge21 learning experience include technology as an integral tool in the learning process and the delivery of content through structured team-based, student-led projects in a physical learning space explicitly designed and configured to support collaborative learning. In the laboratory setting, the learning model has been shown to have a positive impact on students? intrinsic motivation (Lawlor, Marshall & Tangney, 2015), attitudes towards personal learning and ability (Lawlor, Conneely & Tangney, 2010; Sullivan, Marshall & Tangney, 2015), and to positively impact perceptions of computer science (Tangney, Oldham, Conneely, Barrett & Lawlor, 2010). The focus of this research is the progression of the learning model from its initial conception as an innovative outreach project delivered to post-primary students on a university campus, into a school-university partnership aimed at supporting teachers to use the model as a pragmatic approach to designing 21st century learning experiences in school for the formal curriculum. This thesis documents and critically evaluates the iterative design and implementation of a programme, over a four-year period (2010-14), to support teachers to utilise the Bridge21 learning model to teach the formal curriculum in post-primary classrooms in Ireland. The study seeks firstly, to ascertain whether the Bridge21 learning model can be used by a cohort of teachers within the confines of the formal post-primary school system in Ireland and the impact it has on their students and on classroom learning experiences. Secondly, the research aims to explore and define the elements of a conceptual framework to bring a particular model of 21st century learning from its original context in a university laboratory into the authentic setting of school classrooms, with particular focus on the approach to PD for teachers that was conceptualised, trialled and developed during the research. A total of 600 students and 160 teachers from 16 post-primary schools participated in the programme between 2010 and 2014, of which random and opportunistic samples were selected for the purposes of the study. The research follows a critical qualitative approach in a multi-phase mixed methods design, drawing on data from interviews with principals and teachers, questionnaires with teachers and students, along with documentary evidence from the researcher?s journal and field observation notes. The results suggest that the Bridge21 learning model has the potential to be used in post-primary classrooms in Ireland and that such learning experiences can engender the development of key 21st century skills in students. The findings also point towards a number of key features of a conceptual framework for a school-university partnership to support teachers to effectively adopt the Bridge21 model of 21st century learning as a pragmatic approach to teaching the formal curriculum. In particular, several defining characteristics of the model of PD developed during the research process are identified.
Evolution, experiences and evaluation
APPROVED
Keywords: Collaborative learning; Technology-enhanced learning; Education reform; 21st century learning; Teacher professional development; Post-primary education